2018
DOI: 10.1007/s13524-018-0696-1
|View full text |Cite
|
Sign up to set email alerts
|

Father Absence and Accelerated Reproductive Development in Non-Hispanic White Women in the United States

Abstract: Girls who experience father absence in childhood also experience accelerated reproductive development in comparison with peers with present fathers. One hypothesis advanced to explain this empirical pattern is genetic confounding, wherein gene-environment correlation (rGE) causes a spurious relationship between father absence and reproductive timing. We test this hypothesis by constructing polygenic scores for age at menarche and first birth using recently available genome-wide association study results and mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 103 publications
(146 reference statements)
1
34
2
Order By: Relevance
“…For example, for children with genetic factors not associated with early puberty, exposure to ELA characterized by deprivation was associated with testicular maturation 2.3 months earlier than in unexposed peers and onset of thelarche 3.3 months earlier than in unexposed peers. This finding is consistent with research on pubertal timing among children with absent fathers, 37 childhood social disadvantage, 6 , 38 and harsh parenting 39 but contrasts with a previous study by Sumner et al 5 that indicated that early-life exposure to deprivation was not associated with earlier pubertal development (using Tanner stage measurements). However, that study was cross-sectional and operationalized pubertal timing by using self-reported Tanner staging relative to chronological age only among girls.…”
Section: Discussionsupporting
confidence: 84%
“…For example, for children with genetic factors not associated with early puberty, exposure to ELA characterized by deprivation was associated with testicular maturation 2.3 months earlier than in unexposed peers and onset of thelarche 3.3 months earlier than in unexposed peers. This finding is consistent with research on pubertal timing among children with absent fathers, 37 childhood social disadvantage, 6 , 38 and harsh parenting 39 but contrasts with a previous study by Sumner et al 5 that indicated that early-life exposure to deprivation was not associated with earlier pubertal development (using Tanner stage measurements). However, that study was cross-sectional and operationalized pubertal timing by using self-reported Tanner staging relative to chronological age only among girls.…”
Section: Discussionsupporting
confidence: 84%
“…Despite the findings of the literature reviewed above on psychosocial antecedents of pubertal timing, the effects of childhood stress on puberty tend to be relatively small, are somewhat inconsistent across studies, and could reflect gene-environment correlations (rGE) operating on a background of heritable variation in pubertal timing (e.g., Barbaro et al 2017, Mendle et al 2006, Rowe 2000, although initial polygenic analyses have found only limited support for the rGE hypothesis (Gaydosh et al 2018). Theories of differential susceptibility and biological sensitivity to context suggest that the weak main effects of environmental variables on many developmental outcomes may reflect the fact that children differ in whether, how, and how much they are affected by rearing experiences.…”
Section: Importance Of Differential Susceptibility In Regulation Of Pmentioning
confidence: 99%
“…The inferences that can be drawn from human research are also limited by the widespread lack of control for potential genetic confounding in developmental studies that correlate early environmental variables with later outcomes (see Barbaro et al 2017). The problem of genetic confounding has been addressed in a minority of studies (e.g., Ellis et al 2012b, Tither & Ellis 2008; fortunately, more researchers are starting to explicitly incorporate genetic information (e.g., Gaydosh et al 2018), and the results will undoubtedly prompt revisions and refinements of current ideas.…”
Section: Outstanding Questions and Challengesmentioning
confidence: 99%
“…While minor advances in the age of menarche have been observed in the United States and Europe since the 1960s, more dramatic reductions have been observed in countries with improving socioeconomic status such as Indonesia, Brazil, Argentina and China, often in the setting of increased rates of childhood obesity (14,15,16,17,18,19,20). Furthermore, increasing recognition of environmental factors and exposures have been described in association with an earlier age of puberty, such as the effects of maternal smoking during pregnancy, of girls being raised without a father, and of some endocrine-disrupting chemicals (21,22,23).…”
Section: Normal Pubertal Timingmentioning
confidence: 99%